Perencanaan dan Implementasi Perlindungan Perempuan dan Anak Korban Kekerasan di DIY (Studi pada P2TPA â€œRDUâ€ DIY) - Adiyuwana, Yohanes Kristian (Jurnal Ilmiah Administrasi Publik, 2016)
Violence against women and children is deemed as violation of human right and could widely end up affected to the society. This research aims to examine planning of protection for women and children victims in BPPM Province of DIY, implementation of protection for women and children victims in P2TPA RDU Province of DIY, and factors of implementation of protection for women and children victims in P2TPA RDU Province of DIY. Qualitative research approach is used to explore what and how planning and implementation of women and children protection have been conducted. The findings show RKA planning of P2TPA RDU conforms rules of requirements of good planning according to Darwin's (2006), however it does not follow the rule of coordination and participation character. Planning of protection for women and children as violence victim has been implemented and ran well in general. Influenced factors for implementation of protection for women and children as violence victim in P2TPA RDU Provice of DIY, such as communication, resources, disposition, and structure of bureaucracy are running well although not optimum yet.